2021
DOI: 10.3390/jcm11010181
|View full text |Cite
|
Sign up to set email alerts
|

Laser Fiber Displacement Velocity during Tm-Fiber and Ho:YAG Laser Lithotripsy: Introducing the Concept of Optimal Displacement Velocity

Abstract: Background: Endocorporeal laser lithotripsy (EL) during flexible ureteroscopy (URS-f) often uses “dusting” settings with “painting” technique. The displacement velocity of the laser fiber (LF) at the stone surface remains unknown and could improve EL’s ablation rates. This in vitro study aimed to define the optimal displacement velocity (ODV) for both holmium:yttrium-aluminium-garnet (Ho:YAG) and thulium fiber laser (Tm-Fiber). Methods: A 50W-TFL (IRE Polus®, Russia) and a 30W-MH1-Ho:YAG laser (Rocamed®), were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…Under similar settings (0.5 J, 20 Hz) using another laser lithotripter with different pulse profiles, the maximum dusting efficiency could be achieved at even higher v fiber of 10 mm/s (23). However, it should be noted that slow v fiber is much easier to manipulate during clinical LL and preferable over fast scanning speeds to avoid unintentional ureteral wall injury (23).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Under similar settings (0.5 J, 20 Hz) using another laser lithotripter with different pulse profiles, the maximum dusting efficiency could be achieved at even higher v fiber of 10 mm/s (23). However, it should be noted that slow v fiber is much easier to manipulate during clinical LL and preferable over fast scanning speeds to avoid unintentional ureteral wall injury (23).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, careful adjustment of the fiber tip to stone surface distance (or SD) has been recommended for clinical LL (5), and its influence on treatment outcome demonstrated recently in laboratory studies (19,28). Furthermore, scanning the fiber tip over the stone surface may avoid saturation in stone damage when laser pulses are delivered to a fixed spot (23,44). However, the optimal v fiber and SD have not been determined, nor has the associated mechanism of action been elucidated.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…At E p = 0.5 J and F = 20 Hz (with a 230 mm core diameter), Alhoukhi and colleagues compared two clinically relevant fiber scanning speeds and found that the mass loss was much greater at 3 mm/s than at 1 mm/s [ 13 ]. Using similar settings (with a 272 mm core diameter), Panthier et al demonstrated that the maximum stone damage could be produced at v fiber = 10 mm/s or 2.5 mm/s, compared to lower scanning speeds [ 23 ]. Both studies used BegoStone phantoms, yet the mechanism that led to maximum efficiency in stone dusting was not investigated.…”
Section: Introductionmentioning
confidence: 99%